The Impact of Corporate Management and Corporate Structure on Corporate Entrepreneurship: The Mediating Part of HRM Practices - Alkhamis, Faisal (مجلة العلوم الإدارية و الإقتصادية, 2025)
The aim of this research is twofold. First, investigating the effects of both corporate management and corporate structure on corporate entrepreneurship. Second, examining the mediating part of HRM practices in the effects of corporate management and corporate structure on corporate entrepreneurship. Gathering data via a reliable and valid questionnaire developed based on previous related works form a sample of managers selected form service companies, the results, which were obtained by SmartPLS 3.0 software, according to structural equation modeling (SEM) to test the hypotheses. revealed that HRM practices is significantly and positively related to corporate entrepreneurship, both corporate management and corporate structure were significantly and positively related to HRM practices. Also, the results indicated that corporate management had no significant effect on corporate entrepreneurship while the effect of corporate structure on the same dependent construct was negative. Finally, it was found that HRM practices had a full mediation role between corporate management and corporate entrepreneurship whereas HRM practices had no mediating role between corporate structure and corporate entrepreneurship. Based on these results, it was concluded that a key determinant of corporate entrepreneurship, which is corporate management, does not work without effective practices of HRM.